ANALYSIS OF RISK FACTORS FOR PREECLAMPSIA: A CASE–CONTROL STUDY - Indah Lestari; Noer Saudah (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Preeclampsia remains a major contributor to maternal and perinatal morbidity and mortality globally. This study aimed to quantitatively analyze the association between selected maternal risk factors and the occurrence of preeclampsia. A case–control study was conducted involving 120 pregnant women (60 cases and 60 controls) recruited from antenatal care settings. Data were analyzed using chi-square tests and multivariate logistic regression to determine adjusted odds ratios (AOR). The results revealed that obesity (AOR=3.85; 95% CI: 1.72–8.61), chronic hypertension (AOR=4.92; 95% CI: 2.01–12.03), and history of preeclampsia (AOR=5.76; 95% CI: 2.14–15.47) were the most significant predictors. Other variables, such as maternal age, parity, and diabetes mellitus, showed associations in bivariate analysis but lost significance after adjustment. This study confirms that preeclampsia is strongly associated with pre-existing medical conditions and reproductive history. Early risk stratification during antenatal care is essential for prevention and improved maternal outcomes.